Investigating Intermolecular Interactions in a DME-Based Hybrid Ionic Liquid Electrolyte by HOESY NMR - Gyabeng, Derick; Martin, Pierre-Alexandre; Pal, Urbi; Deschamps, Michaël; Forsyth, Maria; O'Dell, Luke A. (Frontiers in Chemistry, 2019)
The intermolecular interactions in a hybrid electrolyte based on various compositions of the ionic liquid N-methyl-N-propyl pyrrolidinium bis-fluorosulfonylimide (C3mpyrFSI), LiFSI salt and an ether-based additive, 1,2-dimethoxy ethane (DME), have been investigated using the HOESY (Heteronuclear Overhauser Effect SpectroscopY) NMR experiment. This NMR technique allows a quantification of the intermolecular interactions in ionic liquids (ILs) by measuring the cross-relaxation rate (σ) between different pairs of nuclei. Thereby, we compare the cross-relaxation rates between the cations, anions and DME in these hybrid electrolyte systems using 1H-7Li and 1H-19F HOESY experiments, and interpret the measured parameters in terms of ionic and molecular associations. The results give insights into the local coordination environment of the Li+ cations and their solvation by the FSI anions and DME.